Dynamic adhesion of polyamide 6, 6 cord/rubber composites in H-pull tests: Fatigue evolution, life prediction and methodology evaluation. (July 2022) - Luo, Ganfang; Zhang, Chi; Huan, Yan; Yin, Yuan; Sun, Hongguo; Chen, Zhaobin; Yang, Xiaoniu
Abstract: The influence of fatigue on adhesion of cord/rubber composites was investigated through H-pull tests. Fatigue was found to promote sulfur diffusion from rubber to RFL and induce modulus homogenizing. Higher frequency caused decrease in fatigue life due to self-heating, but the effect was negligible under low displacement amplitude. Longer fatigue life was achieved at higher R ratio, but an exceptional increase in fatigue life was found at the highest R ratio. A universal CLD model was established for predicting fatigue life. Results of model verification revealed a critical R ratio, above which H-pull test no longer accurately evaluated dynamic adhesion. Highlights: Investigated various fatigue damage modes and their evolution process of polyamide 6, 6 cord/rubber composites in dynamic H-pull tests. Established how frequency and R ratio effect the fatigue of cord/rubber composites. Established a universal CLD model for life prediction involving the effects of frequency and R ratio. Evaluated the feasibility of H-pull test in studying interfacial adhesion of cord/rubber composites under fatigue loadings.